DUTCH DISEASE IN OIL-EXPORTING COUNTRIES: A SURVEY OF THEORY AND EVIDENCE - Czech, Katarzyna (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
Dutch disease phenomenon can be observed in a country that discovers an important and substantial natural resource deposit and starts exporting it on a large scale. In consequence, the country’s currency appreciates reducing competitiveness of its traditional export sector, including agricultural sector. The Dutch disease is considered to be one of the most significant reasons for the natural resource curse. The aim of the paper is to consolidate a growing literature on the Dutch disease and to provide theoretical framework for analysing this phenomenon. It refers to both developed and developing oil-exporting countries. The paper stresses the fact that the vulnerability to the Dutch disease depends strongly on economic policy, political regime and quality of institutions.